Pneumocystis pneumonia with multiple nodules on computed tomography - Saori Ikeda; Noriyo Yanagawa (IDCases)
As is well known to us that pneumocystis pneumonia (PCP) is one of opportunistic infections, there are not so many cases that computed tomography (CT) reveals multiple nodules, especially in non-HIV PCP. In this case, a 47-year-old female with acute myeloid leukemia has developed PCP. Two years prior to this presentation, she had undergone hematopoietic stem cell transplantation (HSCT) and had not experienced any recurrence. CT showed multiple nodules and segmental consolidation with subpleural sparing. Considering that it is refractory to levofloxacin, that β-d glucan is elevated, that PCP PCR was positive in the analysis of bronchial lavage fluid, and that other viral and fungal infections are unlikely, we clinically diagnosed as PCP. Although multiple nodules were thought to be atypical for PCP, CT performed 12 days after starting trimethoprim/sulfamethoxazole to confirm radiological efficacy demonstrated resolution of the nodules as well as consolidation. The significance of the present report lies in the fact that PCP should be kept in mind in the differential diagnosis when there are multiple nodules detected on CT in post-HSCT patients.